The palimpsestuousness of adaptation in James Sturm and Guy Davis' Unstable Molecules: The True Story of Comics' Greatest Foursome. Issue 1 (1st April 2013) - Herd, Damon
This article examines the ways in which James Sturm and Guy Davis have adapted the superhero comic into a biographical comic, and how this process manifests itself in 'palimpsests' visible throughout the adaptation. Written by Sturm, and with art by Davis, Unstable Molecules: The True Story Of Comics' Greatest Foursome (2003) depicts a day in the life of four people who are, according to Sturm's conceit, the real life basis for the main characters in Marvel Comics' The Fantastic Four. First published November 1961, The Fantastic Four marked the beginning of Marvel's so-called 'realistic' depiction of superheroes. In Stan Lee's words 'they'd be flesh and blood, they'd have their faults and foibles, they'd be fallible and feisty, and – most important of all – inside their colorful, costumed booties they'd still have feet of clay'. Sturm presents the events in Unstable Molecules as if they actually happened with notes, biographies and a bibliography to back up his story. He extends Lee's metaphor to show the characters not just as 'flesh and blood' with 'feet of clay' but also lacking any superpowers. In A Theory of Adaptation (2006), Linda Hutcheon discusses the 'palimpsestuousness' of adaptations. She describes this as the 'oscillation between a past image and a present one' that occurs when experiencing an adaptation with a prior knowledge of the work being adapted. To be aware of the original work is to be part of what Hutcheon calls the 'knowing audience'. This article also questions whether Unstable Molecules relies on a 'knowing audience' having a familiarity with The Fantastic Four and whether an 'unknowing audience' might believe the book to be true.